2014
DOI: 10.1164/rccm.201403-0544oc
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin Generation Is Related to Soluble Epoxide Hydrolase Activity in Severe Asthma

Abstract: Rationale: Severe asthma is characterized by airway inflammatory responses associated with aberrant metabolism of arachidonic acid. Lipoxins (LX) are arachidonate-derived pro-resolving mediators that are decreased in severe asthma, yet mechanisms for defective LX biosynthesis and a means to increase LXs in severe asthma remain to be established.Objectives: To determine if oxidative stress and soluble epoxide hydrolase (sEH) activity are linked to decreased LX biosynthesis in severe asthma.Methods: Aliquots of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 42 publications
(75 reference statements)
3
59
1
Order By: Relevance
“…In normal and tumoural mammary tissues, enzymes involved in lipoxin A 4 and RvD 2 synthesis are expressed, with these lipid mediators also reported to display a crucial role in oestrogen-dependent breast cancer progression [38]. In human bronchial explants, it has been demonstrated that LXA 4 mediates beneficial effects via formyl-peptide receptor 2 signalling [39]. This observation is correlated with the ability of LXA 4 to significantly inhibit the platelet-activating factor-induced increases in leukocyte-platelet aggregates and TNF-α-triggered AHR [39].…”
Section: Discussionmentioning
confidence: 99%
“…In normal and tumoural mammary tissues, enzymes involved in lipoxin A 4 and RvD 2 synthesis are expressed, with these lipid mediators also reported to display a crucial role in oestrogen-dependent breast cancer progression [38]. In human bronchial explants, it has been demonstrated that LXA 4 mediates beneficial effects via formyl-peptide receptor 2 signalling [39]. This observation is correlated with the ability of LXA 4 to significantly inhibit the platelet-activating factor-induced increases in leukocyte-platelet aggregates and TNF-α-triggered AHR [39].…”
Section: Discussionmentioning
confidence: 99%
“…Current anti-leukotriene drugs would not be expected to increase lipoxins in asthma. There are likely multiple factors responsible for the defective lipoxin production in SA; however, the increased oxidative stress in SA airways was recently determined to be a major cause of reduced lipoxin generation (11). In human studies, inhaled LXA 4 dampens bronchoprovocation in asthma (10) and lipoxins regulate cytokine-mediated increases in bronchial constriction induced by methacholine, histamine, and thromboxane (11).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…There are likely multiple factors responsible for the defective lipoxin production in SA; however, the increased oxidative stress in SA airways was recently determined to be a major cause of reduced lipoxin generation (11). In human studies, inhaled LXA 4 dampens bronchoprovocation in asthma (10) and lipoxins regulate cytokine-mediated increases in bronchial constriction induced by methacholine, histamine, and thromboxane (11). Recently, a stable LXA 4 analog was shown to markedly decrease allergic inflammation and symptoms in patients with juvenile eczema (37).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have shown that the soluble epoxide hydrolase inhibitors would be of interest because they lead to the activation of endogenous pro-resolving mediators such as lipoxin A4 and epoxyeicosatrienoic acids, while at the same time inhibiting pro-inflammatory pathways [139].…”
Section: New Schemesmentioning
confidence: 99%